PENGARUH LEVERAGE, LIKUIDITAS, UKURAN PERUSAHAAN DAN INVESTMENT OPPORTUNITY SET TERHADAP KUALITAS LABA - Valeria, Valeria; Marpaung, Elyzabet Indrawati (Unversitas Prof. Dr. Moestopo (Beragama), 2024)
Companies need to publish financial reports to inform the financial performance of the company user to the financial report. Companies are likely to manipulate information in their financial reports to attract investors. The company's actual financial performance is reflected in the quality of its earnings. Good earnings quality indicates that the company's profitability is factual and consistent so that investors can trust it. This study aims to examine the effect of leverage, liquidity, company size and investment opportunity set on the quality of the company's earnings. The population in this study were companies in the raw materials, industry, primary and non-primary consumer, and health sectors listed on the Indonesia Stock Exchange during the 2019–2023 period. Sampling in this study used a purposive sampling technique, where samples were taken from a population that met certain criteria. The number of samples in this study that met the criteria was 86 samples from 134 observation samples. Multiple linear regression models were used to analyze the data in this study. The results of this study prove that the leverage variable does not have a significant effect on earnings quality. Meanwhile, the variables liquidity, company size, investment opportunity set, and growth have a significant effect on earnings quality. This research contributes to the development of literature on the topic of earnings quality and provides input to users of corporate financial reports and corporate management to assess or maximize their earnings quality.